Spam and open relay blocking system - Nor Hafizah, Khadzir (2005)
Spam or Unsolicited Bulk Email (UBE) is an electronic mail message that is sent to a large number of recipients who have not requested the message.Spam often contains pornographic, offensive, deceptive and carrying viruses, There are many types of anti-spam had been used to capture the spam but it is still appearing at user mailbox. This is because the settings of the spam filter had been known by spammer. The aim of this project is to develop spam filter that not only can be set by the system but also by the user. Spam and Open Relay Blocking System are antispam software, that will filter e-mail by header and sender that had been set either by user or the system.SORBS may help user through the setting so that user will not lose any white mail.SORBS will be applied at personal computer or notebook.It is through the use of SORES methods that spam can be reduced from entering the user mailbox. Besides, setting that had been done and only known by the user make spammer take time to attack the user e-mail filter.